Keeping Online Asynchronous Discussions on Topic - Beaudin, Bart P. (Online Learning, 1999)
The purpose of this research was to identify various techniques recommended and used by online instructors for keeping online learners on topic during asynchronous discussion and to identify what factors affected selection. A thirty-seven item online questionnaire was developed and completed by 135 online instructors subscribing to an international distance education listserv. Thirteen techniques for keeping online asynchronous learners on topic were rated using a sixpoint Likert scale. The results of the study showed that online instructors rated the following as the top four techniques for keeping asynchronous online discussion on topic: 1) Carefully design questions that specifically elicit on-topic discussion, 2) provide guidelines to help online learners prepare on-topic responses, 3) reword the original question when responses are going in the wrong direction and 4) provide discussion summary on a regular basis. Experience, training and differences between what respondents recommended and used to keep online asynchronous discussion on topic produced statistically significant results at the 0.05 level.